(3fRgI GdeLGdS aj fNHI GdeLGdSs - (3Ydj Hf YeQ Hf EHQGgje GdcfGfj, CHh GdMSfs
(3ChdgG (B:s
(3hHYO agPG cJGH jMJhi Ydi YTQjf eLdS ai GdehGYX s
(3BNQgG (B:s
(3JeJ GdeLGdS HMeO Gddg JYGdi hMSf Yhfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B(94) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs